Micro-Strip Antenna Array for Telecommunication Systems - Alkhawaldeh, igried (European Journal of Applied Sciences, 2022)
Broadband and dual-band micro strip antenna for telecommunication systems, this paper construction of a broadband micro strip antenna for airborne telecommunication systems are described. Considered antenna represented modified broad-band antenna of butterfly-style. The electro-dynamic numerical simulation results are obtained; the parameters and the basic characteristics of antenna are determinate, currently widespread practical application got multiband and broadband radio systems. The technical characteristics of such systems are largely determined by characteristics of antenna-feeder devices. This paper presents a literature survey of slotted microstrip patch antenna's the are dual band